1976
DOI: 10.1021/j100551a018
|View full text |Cite
|
Sign up to set email alerts
|

Proton diffusion and activity in the presence of electrolytes

Abstract: The ESR spectra were recorded on an x-band E-9 ESR spectrometer. The temperature was controlled with a Varían V-4557 variable-temperature controller calibrated with an iron constantan thermocouple. The method used to determine the thermodynamic parameters for the dissociation of the p -benzosemiquinone ion pair (eq 1) was exactly the same as previously described.7®Care must be taken in the handling of HMPA, since it has been found to be a possible carcinogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…According to Patachia et al and Tretinnikov et al , the potassium ion acts as a “structure breaker,” the opposite of calcium as a “structure maker.” Therefore, when potassium chloride is added to the system, potassium ions will shield PVA hydroxyl groups from water molecules and break water–water hydrogen bonding. , Roberts states that water can more freely rotate when structure breakers like potassium are present in solution and lattice structures are broken, which in aqueous solutions has been shown to decrease hydronium diffusivity. However, in the case of this study, an increase in diffusivity was observed, which can potentially be explained by potassium ions interacting more favorably with PVA hydroxyl groups over water.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Patachia et al and Tretinnikov et al , the potassium ion acts as a “structure breaker,” the opposite of calcium as a “structure maker.” Therefore, when potassium chloride is added to the system, potassium ions will shield PVA hydroxyl groups from water molecules and break water–water hydrogen bonding. , Roberts states that water can more freely rotate when structure breakers like potassium are present in solution and lattice structures are broken, which in aqueous solutions has been shown to decrease hydronium diffusivity. However, in the case of this study, an increase in diffusivity was observed, which can potentially be explained by potassium ions interacting more favorably with PVA hydroxyl groups over water.…”
Section: Resultsmentioning
confidence: 99%
“…However, one or both mechanisms are likely hindered within hydrogels since diffusivity in all the hydrogels tested exhibited a slower effective diffusivity than aqueous hydronium diffusion. Roberts 35 found that electrostatic interactions could hinder hydronium transport in aqueous systems, leaving Brownian motion to be the dominant mechanism for diffusion. This result is possible in hydrogel systems too due to the competing interactions from polymer−solvent and solvent−solute interactions and may explain how the Grotthuss mechanism is hindered.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several materials crystallize with the prototype AuCu structure, but only three binary superconductors of this structure are reported [2,3]. They are: BaBi 3 (T c =5.69 K), BiNa (T c =2.25 K), BiLi (T c =2.47 K) [2].…”
Section: Introductionmentioning
confidence: 99%